PROSES BERPIKIR TINGKAT TINGGI SISWA SMP DALAM MENYELESAIKAN SOAL PISA DAN SCAFFOLDINGNYA - Siti Fatimah; Gatot Muhsetyo; Swasono Rahardjo (FMIPA UNIVERSITAS NEGERI MALANG, 2021)
Indonesia's PISA test results in the last three periods still rank in the bottom ten. This shows that the mathematics ability of Indonesian students is still low. This research aims to explore the higher order thinking processes experienced by junior high school students in solving PISA questions before and during scaffolding. This research was conducted at SMP Negeri 3 Singosari, Malang Regency, in the form of giving tests to 31 students of class IX, interviews and scaffolding. Scaffolding is done in order to complete the unfulfilled aspects in the phases of thinking. From this research, it was found that: (1) The high-level thinking process of students in solving PISA questions, before scaffolding has included the three phases that must be passed (the entry phase, the attack phase, and the review phase), but not all aspects of each phase are fulfilled; (2) Scaffolding has helped students in solving PISA questions. Improve the teacher's ability to do scaffolding to help students find aha! with more attention to the obstacles (stuck?) faced by students